Nasionalisme Relijius sebagai Strategi Dakwah Struktural - Subandi, Bambang (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
Structural Da'wa is characterized by strengthening the Da'wa message on the power structure. Religious nationalism is a form of structural Da'wa strategy appropriate for plural societies such as the Indonesian people. It emerged from resistance to colonization. In Indonesia, religious nationalism played a role in the formation of a constitution that formulated